Phosphorylated CRMP1, axon guidance protein, is a component of spheroids and is involved in axonal pathology in amyotrophic lateral sclerosis - Kawamoto, Yuko; Tada, Mikiko; Asano, Tetsuya; Nakamura, Haruko; Jitsuki-Takahashi, Aoi; Makihara, Hiroko; Kubota, Shun; Hashiguchi, Shunta; Kunii, Misako; Ohshima, Toshio; Goshima, Yoshio; Takeuchi, Hideyuki; et al. (Frontiers in Neurology, 2022)
In amyotrophic lateral sclerosis (ALS), neurodegeneration is characterized by distal axonopathy that begins at the distal axons, including the neuromuscular junctions, and progresses proximally in a “dying back” manner prior to the degeneration of cell bodies. However, the molecular mechanism for distal axonopathy in ALS has not been fully addressed. Semaphorin 3A (Sema3A), a repulsive axon guidance molecule that phosphorylates collapsin response mediator proteins (CRMPs), is known to be highly expressed in Schwann cells near distal axons in a mouse model of ALS. To clarify the involvement of Sema3A–CRMP signaling in the axonal pathogenesis of ALS, we investigated the expression of phosphorylated CRMP1 (pCRMP1) in the spinal cords of 35 patients with sporadic ALS and 7 disease controls. In ALS patients, we found that pCRMP1 accumulated in the proximal axons and colocalized with phosphorylated neurofilaments (pNFs), which are a major protein constituent of spheroids. Interestingly, the pCRMP1:pNF ratio of the fluorescence signal in spheroid immunostaining was inversely correlated with disease duration in 18 evaluable ALS patients, indicating that the accumulation of pCRMP1 may precede that of pNFs in spheroids or promote ALS progression. In addition, overexpression of a phospho-mimicking CRMP1 mutant inhibited axonal outgrowth in Neuro2A cells. Taken together, these results indicate that pCRMP1 may be involved in the pathogenesis of axonopathy in ALS, leading to spheroid formation through the proximal progression of axonopathy.